2003
DOI: 10.1029/2001jb001172
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and tectonics of the Mid‐Atlantic Ridge, 7°–12°S

Abstract: [1] We present swath bathymetric, gravity, and magnetic data from the Mid-Atlantic Ridge between the Ascension and the Bode Verde fracture zones, where significant ridge-hot spot interaction has been inferred. The ridge axis in this region may be divided into four segments. The central two segments exhibit rifted axial highs, while the northernmost and southernmost segments have deep rift valleys typical of slow-spreading mid-ocean ridges. Bathymetric and magnetic data indicate that both central segments have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 54 publications
3
51
1
1
Order By: Relevance
“…Here we present a systematic study of the residual mantle Bouguer gravity anomaly of 19 oceanic transform faults that reveals a strong correlation between gravity signature and spreading rate. Previous studies have shown that slow-slipping transform faults are marked by more positive gravity anomalies than their adjacent ridge segments 1,2,4,6 , but our analysis reveals that intermediate and fast-slipping transform faults exhibit more negative gravity anomalies than their adjacent ridge segments. This finding indicates that there is a mass deficit at intermediate and fast-slipping transform faults, which could reflect increased rock porosity, serpentinization of mantle peridotite, and/or crustal thickening.…”
Section: Chaptercontrasting
confidence: 50%
See 1 more Smart Citation
“…Here we present a systematic study of the residual mantle Bouguer gravity anomaly of 19 oceanic transform faults that reveals a strong correlation between gravity signature and spreading rate. Previous studies have shown that slow-slipping transform faults are marked by more positive gravity anomalies than their adjacent ridge segments 1,2,4,6 , but our analysis reveals that intermediate and fast-slipping transform faults exhibit more negative gravity anomalies than their adjacent ridge segments. This finding indicates that there is a mass deficit at intermediate and fast-slipping transform faults, which could reflect increased rock porosity, serpentinization of mantle peridotite, and/or crustal thickening.…”
Section: Chaptercontrasting
confidence: 50%
“…Slow-spreading mid-ocean ridge segments exhibit significant crustal thinning towards transform and non-transform offsets [1][2][3][4][5][6][7][8][9][10][11][12] , which is thought to arise from a three-dimensional process of buoyant mantle upwelling and melt migration focused beneath the centres of ridge segments 1,2,[4][5][6][7]9,10,12 . In contrast, fast-spreading midocean ridges are characterized by smaller, segment-scale variations in crustal thickness, which reflect more uniform mantle upwelling beneath the ridge axis [13][14][15] .…”
Section: Chaptermentioning
confidence: 99%
“…The systems are therefore fundamentally different. An example of a migrating oblique discontinuity is the northward propagating Mid-Atlantic Ridge segment between 8 • S and 9 • S, whose morphology, structure and tectonics are described in detail by Bruguier et al (2003) and Minshull et al (2003). The discontinuity has a small offset (10-15 km) and there is no sheared zone, giving strong evidence that older lithosphere is not ruptured as the discontinuity migrates.…”
Section: Kinematics Of the Tammar Propagating Rift 1383mentioning
confidence: 99%
“…Segment A3 is the shallowest segment, with crustal thicknesses up to 11 km [Bruguier et al, 2003]. The axial region is characterized by extensive sheet flows and the virtual absence of "hummocky terrain, " which is the surface expression of pillow volcanoes and a typical feature of slow spreading ridges.…”
Section: Six-year Effort On the Mid-atlantic Ridgementioning
confidence: 99%
“…Previous studies [Bruguier et al, 2003;Minshull et al, 1998] had divided this area into four major segments, A1-A4 (see Figure 1). The widely varying topography and crustal thicknesses suggested that rates of magma supply differ greatly from one segment to another.…”
Section: Six-year Effort On the Mid-atlantic Ridgementioning
confidence: 99%